2015
DOI: 10.1038/nature14559
|View full text |Cite
|
Sign up to set email alerts
|

UbiX is a flavin prenyltransferase required for bacterial ubiquinone biosynthesis

Abstract: Ubiquinone, or coenzyme Q, is a ubiquitous lipid-soluble redox cofactor that is an essential component of electron transfer chains1. Eleven genes have been implicated in bacterial ubiquinone biosynthesis, including ubiX and ubiD, which are responsible for decarboxylation of the 3-octaprenyl-4-hydroxybenzoate precursor2. Despite structural and biochemical characterization of UbiX as an FMN-binding protein, no decarboxylase activity has been detected3–4. We report here that UbiX produces a novel flavin-derived c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
199
7
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(211 citation statements)
references
References 29 publications
2
199
7
3
Order By: Relevance
“…Recently, it has been demonstrated that Fdc1 and its bacterial homologue UbiD perform the actual decarboxylase function, whereas Pad1 and its bacterial homologue UbiX are responsible for the prenylation of flavin mononucleotide (FMN), leading to the generation of a cofactor required for decarboxylase function (13,27,28). In contrast to Fdc1/Pad1, UbiD/UbiX is involved in the biosynthesis of ubiquinone in E. coli.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been demonstrated that Fdc1 and its bacterial homologue UbiD perform the actual decarboxylase function, whereas Pad1 and its bacterial homologue UbiX are responsible for the prenylation of flavin mononucleotide (FMN), leading to the generation of a cofactor required for decarboxylase function (13,27,28). In contrast to Fdc1/Pad1, UbiD/UbiX is involved in the biosynthesis of ubiquinone in E. coli.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, a prenyltransferase UbiX from P. aeruginosa involved in the biosynthesis of ubiquinones was demonstrated to use flavin as a prenyl acceptor. In contrast to prenyl diphosphates for other known prenyltransferases, dimethylallyl monophosphate (DMAP) serves as prenyl donor for UbiX reaction (White et al 2015).…”
Section: Membrane-bound Prenyltransferases For Aromatic Substratesmentioning
confidence: 99%
“…It has been shown that ubiX and ubiD genes are involved in the decarboxylation of UQ aromatic ring in bacteria (Meganathan, 2001; Gulmezian et al, 2007; Aussel et al, 2014). ubiX encodes a flavin mononucleotide (FMN)-binding protein with no decarboxylase activity detected in vitro (Gulmezian et al, 2007; Aussel et al, 2014), and UbiX proteins are metal-independent and require dimethylallyl-monophosphate as substrate (White et al, 2015). During the biosynthesis of UQ, UbiX acts as a flavin PT, producing a flavin-derived cofactor required for the decarboxylase activity of UbiD (Payne et al, 2015; White et al, 2015).…”
Section: Enzymes and Their Encoding Genes Involved In Pq And Uq Biosymentioning
confidence: 99%
“…ubiX encodes a flavin mononucleotide (FMN)-binding protein with no decarboxylase activity detected in vitro (Gulmezian et al, 2007; Aussel et al, 2014), and UbiX proteins are metal-independent and require dimethylallyl-monophosphate as substrate (White et al, 2015). During the biosynthesis of UQ, UbiX acts as a flavin PT, producing a flavin-derived cofactor required for the decarboxylase activity of UbiD (Payne et al, 2015; White et al, 2015). pad1 and fdc1 are two fungal genes related to bacterial ubiX and ubiD (Mukai et al, 2010; Lin et al, 2015; Payne et al, 2015).…”
Section: Enzymes and Their Encoding Genes Involved In Pq And Uq Biosymentioning
confidence: 99%